Non-invasive Hall probe measurements of the lateral current distribution in BSCCO/Ag conductors. - Johnston, MD; Everett, J; Dhalle, M; Grasso, G; Flukiger, R; Yang, M; Grovenor, C; Caplin, A (1995)
Using a 100 mu m resolution scanning Hall probe, we have measured the self-field profile due to a transport current in BSCCO/Ag 2223 and 2212 conductors. The field component perpendicular to the plane of the tape after analysis yields the lateral current distribution. In the 2212 samples this distribution becomes uniform (on the experimental length scale) at high currents. At lower currents the distribution shifts towards the sample edges as predicted theoretically for homogenous type II superconducting strips. The expected remanent current profiles after the external current has been switched off are also measured. In the 2223 tape, the current is found to be concentrated at the sample edges.